RESPIRATION AND VIABILITY OF STORED RADISH SEEDS DUE TO SEED BORNE ASPERGILLUS FLAVUS - B. K. PRASAD, R. N. SAO*, R. N. SINGH, N. NARAYAN, S. P. SINGH, S. KUMAR AND (Indian Phytopathology, 2002)
The 0, uptake of radish cv Pusa Reshmi seeds increased due to seed-borne Aspergillus flavus with extension of the storage period upto twenty days and at specified as well as increased level of RH. The loss in dry weight and germination of seeds were also inflated with rise in RH level and duration of storage. The .ectivitv of starch phosphorylase, fructose diphosphate aldolase; pyruvic, a-ketoglutaric and succinic acid dehydrogenase, peroxidase, ascorbic acid oxidase, catalase and ATPase was enhanced besides increase in pyruvic acid and total keto acid and decrease in a-ketoglutaric acid.